KONSEP BIMBINGAN DAN KONSELING ISLAM DALAM SURAH AT-TAHRIM AYAT 6 - S Sabarrudin; Hasan Zaini; I Irman (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
Interpretation of the verses of the Qur'an is very important, especially its use in the world of Islamic guidance and counseling, because the interpretation of the verses of the Qur'an can be used by counselors in overcoming client problems. This study aims to describe the concept of Islamic guidance and counseling in surah At-Tahrim Verse 6. This research was conducted through a literature review. The results of the study show that the concept of Islamic guidance and counseling is in accordance with Surah At-Tahrim verse 6 namely